Generation of Neurospheres from Human Adipose-Derived Stem Cells. (26th February 2015) - Yang, Erfang; Liu, Na; Tang, Yingxin; Hu, Yang; Zhang, Ping; Pan, Chao; Dong, Shasha; Zhang, Youping; Tang, Zhouping
Abstract : Transplantation of neural stem cells (NSCs) to treat neurodegenerative disease shows promise; however, the clinical application of NSCs is limited by the invasive procurement and ethical concerns. Adipose-derived stem cells (ADSCs) are a source of multipotent stem cells that can self-renew and differentiate into various kinds of cells; this study intends to generate neurospheres from human ADSCs by culturing ADSCs on uncoated culture flasks in serum-free neurobasal medium supplemented with B27, basic fibroblast growth factor (bFGF), and epidermal growth factor (EGF); the ADSCs-derived neurospheres were terminally differentiated after growth factor withdrawal. Expression of Nestin, NeuN, MAP2, and GFAP in ADSCs and terminally differentiated neurospheres was shown by quantitative reverse transcription-polymerase chain reaction (qRT-PCR), western blotting, and immunocytochemistry; cell proliferation in neurospheres was evaluated by cell cycle analyses, immunostaining, and flow cytometry. These data strongly support the conclusion that human ADSCs can successfully differentiate into neurospheres efficiently on uncoated culture flasks, which present similar molecular marker pattern and proliferative ability with NSCs derived from embryonic and adult brain tissues. Therefore, human ADSCs may be an ideal alternative source of stem cells for the treatment of neurodegenerative diseases.